262 Full Cycle Audit on Definitive Management of Biliary Pancreatitis. (28th February 2022) - Islam, R.; Hashmi, Z.Z.; Aljarad, F.; Madanur, M.A.; Imtiaz, N.; Warren, R.
Abstract: Aim: To reaudit the practice of definitive management of gall stones pancreatitis in our trust for the period of 1st May-31st October and compare the result with previous one (1st June 2019–31st Dec 2019). Method: It was a retrospective collection of data of patients admitted to our trust with biliary pancreatitis. Electronic notes, PACS for US report, Electronic discharge summary and Operative notes analysed. Results: We identified 4 patients admitted with biliary pancreatitis during the re-audit period. US report was checked for confirmation of diagnosis of gall stones. The EDN was checked for date for Laparoscopic cholecystectomy. Unfortunately, none of them had their procedure time in 2 weeks' time of their diagnosis. The reason behind this was because of COVID-19 pandemic, we were backlogging with our elective list. All the patients eventually underwent their procedure, but not in 2 weeks' time as per the guidelines. All suitable patients had their cholecystectomy in a timely manner during first audit. None had it in timely manner during second audit. Conclusions: Early Laparoscopic cholecystectomy for simple gallstone pancreatitis prevents life threatening Pancreatitis and readmissions. The UK guidelines on management of pancreatitis issued by British society guidelines (BSG) states that all mild gall stones pancreatitis should have definitive management of lithiasis on the same admission or within 2 weeks (Recommendation B). In our practice, all our suitable patients during first audit had timely Laparoscopic cholecystectomy, however, no one had it in timely manner on the next audit for COVID-19 pandemic.